1977
DOI: 10.1002/1097-0142(197711)40:5<2087::aid-cncr2820400516>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer mammography patterns

Abstract: Mammography studies, from 1963 through 1972, on 5,918 women over age 30 years with 327 breast cancer on initial studies, were prospectively categorized on a scale of 1 to 4 of increasing amounts of fibroglandular tissue. Approximately 60% of the cancers occurred in classes 1 and 2 breasts, about one-third of the patients, while 40% of the cancer were in the remaining two-thirds, comprising classes 3 and 4. There were 54 cancers that developed in breast that previously were free of symptoms, clinical signs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 4 publications
1
39
0
1
Order By: Relevance
“…It has been suggested that the apparent risk of breast cancer associated with the mammographic patterns described by Wolfe is an artefact arising from the concealmaent of breast cancer by the radiologically denser P2 and DY patterns (Egan & Mosteller, 1977 (Shapiro, 1977) Finally, bias in the classification of mammograms was avoided in this study by concealing from the radiologists which mammograms were from cases and which from controls.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been suggested that the apparent risk of breast cancer associated with the mammographic patterns described by Wolfe is an artefact arising from the concealmaent of breast cancer by the radiologically denser P2 and DY patterns (Egan & Mosteller, 1977 (Shapiro, 1977) Finally, bias in the classification of mammograms was avoided in this study by concealing from the radiologists which mammograms were from cases and which from controls.…”
Section: Discussionmentioning
confidence: 89%
“…A number of other studies have shown these categories to be associated with different risks for the development of breast cancer (Egan & Mosteller, 1977;Egan & McSweeney, 1979;Krook et al, 1978;Krook, 1975;Threatt et al, 1980;Hainline et al, 1978, Wilkinson et al, 1977Brebner et al, 1978;Chaffe et al, 1979) and have in general confirmed that higher risk is associated with the P2 and DY categories. In another paper (Boyd et al, 1982) we have shown that there is a relationship between symptoms of breast disease and the DY pattern in the absence of breast cancer, and have suggested that some negative reports of the association between Wolfe's patterns and breast cancer may have arisen because of the inclusion of subjects with symptoms (Kessler & Fischedick, 1980;Mendell et al, 1977;Rideout, 1977;Peyster et al, 1977;Doyle et al, 1979).…”
mentioning
confidence: 91%
“…In this conventional case -control study, the effects of masking (Eagan and Mosteller, 1977) are different from cohort studies. If masking of cancer by breast density leads to the under-diagnosis of breast cancer, cases with high breast density will be underrepresented among the diagnosed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report the incidence of breast cancer in a cohort of women classified according to their initial mammographic characteristics (Egan & Mosteller, 1977;Egan & McSweeney, 1979;Krook et al, 1978;Krook, 1978;Threatt et al, 1980;Moskowitz et al, 1980;Ernster et al, 1980). In others, the prevalence of breast cancer detected at the first examination within each category of mammographic pattern is described (Egan & Mosteller, 1977;Krook, 1978;Kessler & Fischedick, 1980).…”
mentioning
confidence: 99%
“…In others, the prevalence of breast cancer detected at the first examination within each category of mammographic pattern is described (Egan & Mosteller, 1977;Krook, 1978;Kessler & Fischedick, 1980). Still others have used a case-control design, not always with a formally constituted control group, in which the prevalence of each mammographic pattern in a group of women with diagnosed breast cancer is compared to that of controls (Mendell et al, 1977;Rideout & Poon, 1977;Hainline et al, 1978;Wilkinson et al, 1977;Doyle et al, 1-979;Chaffe et al, 1979 (Boyd etal., 1982).…”
mentioning
confidence: 99%